Dichloroacetate Overcomes Oxaliplatin Chemoresistance in Colorectal Cancer through the miR-543/PTEN/Akt/mTOR Pathway - Liang, Yu (J Cancer, 2019)
Chemoresistance is responsible for most colorectal cancer (CRC) related deaths. In this study, we found that dichloroacetate (DCA), a pyruvate dehydrogenase kinase (PDK) inhibitor, can be used as a sensitizer for oxaliplatin (L-OHP) chemoresistant CRC cells. The aim of this study was to explore the ability of DCA to overcome L-OHP resistance in CRC cells and to identify the underlying molecular mechanisms. We found that DCA sensitizes chemoresistant CRC cells to L-OHP-induced cytotoxic effects by inhibiting clone formation capacity and promoting cell apoptosis. A microRNA (miRNA) array was used for screen, and miR-543 was identified and shown to be downregulated after DCA treatment. The expression of miR-543 was higher in chemoresistant CRC cells than in chemosensitive CRC cells. Overexpression of miR-543 increased chemoresistance in CRC cells. The validated target gene, PTEN, was negatively regulated by miR-543 both in vitro and in vivo, and PTEN was upregulated by DCA through miR-543. In addition, overexpression of miR-543 reversed the inhibition of colony formation after DCA treatment. Furthermore, the Akt/mTOR pathway is activated by miR-543 and is involved in the miR-543 induced chemoresistance. There was a significant inverse relationship between miR-543 expression and PTEN level in CRC patients, and high miR-543 expression was associated with worse prognosis. In conclusion, DCA restored chemosensitivity through miR-543/PTEN/Akt/mTOR pathway, and miR-543 may be a potential marker or therapeutic target for chemoresistance in CRC.